The Effect of Rewards on Employee Performance in the Future New Normal At Pt. Slj Global Tbk in Samarinda City - Aswan, Aswan; Anitra, Vera; Anam, Khairul (Indonesian Operations Research Association (IORA), 2022)
The purpose of this study was to determine whether there is an influence between the giving of rewards to the performance of employees in the New Normal period at PT. SLJ GLOBAL TBk Samarinda. In this study, the population selected in the production office was 100 people. The sampling technique used in this study is probability sampling with a total sample of 80 people. The data analysis technique used is the Simple Regression Analysis technique with the results that there is an influence between the variables of giving rewards to employee performance, it can be seen in the value of the coefficient of determination (R2) which is 0.904, so from these results it can be concluded that reward giving is influenced by employee performance by 90% while 10% is influenced by other variables not included in this study. The awarding of rewards obtained t-count greater than t-table of 27,163 > 1,991 with a significant level of result of 0.000 < 0.05 (Î± = 0.05). Theoretical benefits of research Provide analytical information that the research can provide benefits in the development of studies regarding the effect of reward giving on employee performance in the New Normal period. Meanwhile, practically for companies, it is hoped that this research will help companies analyze existing rewards in the company and be able to provide suggestions to get input on giving rewards to companies.